5(x+6)-7x=26

Simple and best practice solution for 5(x+6)-7x=26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x+6)-7x=26 equation:


Simplifying
5(x + 6) + -7x = 26

Reorder the terms:
5(6 + x) + -7x = 26
(6 * 5 + x * 5) + -7x = 26
(30 + 5x) + -7x = 26

Combine like terms: 5x + -7x = -2x
30 + -2x = 26

Solving
30 + -2x = 26

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + -2x = 26 + -30

Combine like terms: 30 + -30 = 0
0 + -2x = 26 + -30
-2x = 26 + -30

Combine like terms: 26 + -30 = -4
-2x = -4

Divide each side by '-2'.
x = 2

Simplifying
x = 2

See similar equations:

| 3w+13=34 | | 7m-10=9m+4 | | 20x-7=3+18 | | .72x+2.4x+32.58=.89x-.55x | | -2t+7=5t | | -3f=-f-10 | | x-8=-2x+3 | | -10u=-9-9u | | -4(x-3)-3x=2(6-3x)-3x | | -6+14+4=32 | | W+(w+2)=-27 | | 10+6z=5z | | 9p-10=10p | | 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 | | 4x^2+3x^2-2x=0 | | 2=X+3x^2 | | -3(7n+4)=-2n+26 | | F(19)=4x+7 | | 256=(-4)x | | 0=-10k+5k | | x=-2+8 | | 5x+2(x+4)=5(2x+10) | | 3(-6-7b)=4(-5b-6) |

Equations solver categories